STUDY OF THE REFLECTION OF THE ULTRASONIC WAVE IN THE TIME DOMAIN - LOUANI, Kahina (Journal of Human Sciences, 2021)
The characterization of the sound field by means of numeral calculation allows to examine certain fundamental problems of the diffraction in the case of the reflection of the impulsive wave. The harmonious wave introduced originally in optics is replaced by an infinitely brief wave or an impulse of Dirac and thus the calculations are led in the temporal domain. A clear physical interpretation of these results explains the mechanism of this reflection on a record then on a limited target. In application, we chose various signals of entered then, by convolution digital technology, we find the form of the signal corresponding to the thoughtful wave.